First Record of Pygidiopsis summa and Ascocotyle longa in Iraq: Catatan Pertama Pygidiopsis summa dan Ascocotyle longa di Irak - Ghadeer M. Al-Suwaij; Basim H. Abdullah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Heterophyid flukes are zoonotic parasites with complex life cycles involving multiple hosts, including fish and mammals, and pose significant public health risks. Specific Background: Despite global studies on heterophyid infections, their presence in Iraq has not been previously documented. Knowledge Gap: There is a lack of data on the distribution, taxonomy, and potential health implications of these parasites in the region. Aims: This study reports the first record of Pygidiopsis summa and Ascocotyle longa in Iraq, providing taxonomic descriptions and assessing their significance. Results: A total of 150 Rattus norvegicus were captured in Basrah, and their small intestines were examined, revealing both fluke species. Morphological analysis showed slight variations in spine length. Novelty: This is the first documentation of these species in Iraq. Implications: Findings highlight the need for awareness of foodborne parasitic infections and further molecular and epidemiological studies on heterophyid transmission dynamics. Highlights: First record of Pygidiopsis summa and Ascocotyle longa in Iraq. Highlights Rattus norvegicus as a potential reservoir for heterophyid flukes. Emphasizes foodborne parasitic risks, urging further molecular and epidemiological studies. Keywords: wild rat, Pygidiopsis summa, Ascocotyle longa, Basrah